Maternal attachment, peer relationship and behavior problems among primary school children - Afandi, Aqilah Abu Hasan; Ismail, Nellie (Human Resource Management Academic Research Society, 2022)
Behavior problems that occur during childhood often persist into adolescence and they can also lead to various negative outcomes. Since mothers and peers play a significant role in developing children’s behavior, this study aimed to determine the relationship between maternal attachment and peer relationship with behavior problems among children. A total of 440 children aged between 10 to 11 were chosen by using the multistage cluster sampling technique. The data for this study were collected by using a self-administered questionnaire. The result indicated that maternal attachment posed a significantly negative relationship with behavior problems. The result also indicated that peer relationship was significantly and positively correlated with behavior problems. Meanwhile, multiple regression outcomes showed that peer relationships yielded the strongest influence on behavior problems. In conclusion, a good peer relationship is crucial to overcoming behavior problems among primary school children.